2010
DOI: 10.1016/j.icarus.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Penetrometry of granular and moist planetary surface materials: Application to the Huygens landing site on Titan

Abstract: 46The Huygens probe landed on the then unknown surface of Titan in January 2005. A 47 small, protruding penetrometer, part of the Surface Science Package (SSP), was pushed into the 48 surface material measuring the mechanical resistance of the ground as the probe impacted the 49 landing site. We present laboratory penetrometry into room temperature surface analogue 50 materials using a replica penetrometer to investigate further the nature of Titan's surface and 51 examine the sensor's capabilities. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
4
29
1
Order By: Relevance
“…A notable feature in the penetrometry data, over the first five centimetres of penetration, is a negative force-depth gradient that Atkinson et al (2010) reproduced in the laboratory with penetrometer impacts into coarse wet sand. Atkinson et al (2010) also investigated the particle size at the Huygens site and found that their data was consistent with a particle diameter of 2 mm but noted that larger particles may exist at the site as seen in the Huygens imager data (Keller et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…A notable feature in the penetrometry data, over the first five centimetres of penetration, is a negative force-depth gradient that Atkinson et al (2010) reproduced in the laboratory with penetrometer impacts into coarse wet sand. Atkinson et al (2010) also investigated the particle size at the Huygens site and found that their data was consistent with a particle diameter of 2 mm but noted that larger particles may exist at the site as seen in the Huygens imager data (Keller et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…The prominent features of the data, relevant to this study, are labelled. The feature labelled A is a low strength material that has been associated with a loose covering of deposited material (Atkinson et al, 2010) most likely airfall dust (Schröder et al, 2012). The feature labelled B is a peak, possibly caused by the impact with one of the ice pebbles observed on the surface.…”
Section: Regolith Structure and Microstructure Measured By A Landing mentioning
confidence: 99%
See 3 more Smart Citations